A Study on the Cognition and Emotion Identification of Participative Budgeting Based on Artificial Intelligence - Zhou, Yuan; Zhang, Tianjiao; Zhang, Lan; Xue, Zhaoxin; Bao, Mingxu; Liu, Lingbing (Frontiers in Psychology, 2022)
Cognition and emotion exert a powerful influence on human behavior. Based on cognitive psychology and organizational behavior theory, this paper examines the role of cognition and emotion in participative budgeting and corporate performance using a questionnaire survey. The questionnaires were sent to 345 listed companies in China. The results support the hypothesis that human cognition and emotion have a positive moderating effect on the relationship between participative budgeting and corporate performance. Cognition and emotion can promote the effect of participative budgeting on corporate performance. Furthermore, according to the theory of artificial intelligence (AI), this paper designs an AI-based cognition and emotion identification system. This system can help managers identify the budget participants’ cognitive and emotional states and undertake the interventions necessary to improving corporate performance.